Composition of Extracellular Polymeric Substances (EPS) produced by Flavobacterium columnare isolated from tropical fish in Brazil - Sebastião, Fernanda De Alexandre [UNESP]; Pilarski, Fabiana [UNESP]; Lemos, Manoel Victor Franco [UNESP] (Sociedade Brasileira de Microbiologia, 2013)
Thirty nine isolates of Flavobacterium columnare from Brazilian fish farms had their carbohydrate composition of EPS evaluated by high efficiency liquid chromatography, using the phenol-sulfuric acid method of EPS. The occurrence of capsules on F. columnare cells was not directly related to biofilm formation, and the predominant monosaccharide is glucose.
Keywords: biofilm; extracellular polymeric substances; Flavobacterium columnare; fish